Philosophy of education : major themes in the analytical tradition Volume II : Education and human being (London ; New York : Routledge, 1998)
Education and autonomy. Education and the development of mind. Intelligence, emotions, imagination and education. Needs, interests, happiness and education.
Keywords: Education; Critical pedagogy; Philosophy; Education -- Philosophy; Critical pedagogy -- Philosophy; Educational sociology